2022
DOI: 10.24925/turjaf.v10i12.2358-2367.5460
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Tolerances of Some Cotton Genotypes Against Wilt Disease (Verticillium dahliae Kleb.) Under The Ecological Conditions of Diyarbakir

Abstract: Verticillium wilt disease in cotton is a soil-borne disease that causes significant yield losses, and it is therefore important to identify disease-resistant genotypes. Current study was carried out in the experimental field of the Faculty of Agriculture, Dicle University (Diyarbakir) in the year 2020 to determine the tolerance levels of some cotton genotypes which contain different characteristics to wilt disease (Verticillium dahliae Kleb.). The experiment area has been naturally infected with Verticillium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Genotypes for FDI at the boll opening stage of 50-60%, ranged from 0.71 for an inbred line called 58 to the value of 1.15 for the Çukurova-1518 variety. According to Baran (2022), the leaf-disease severity varied between 0.12-3.09 at 50-60% at the boll opening period, whilst stem crosssection values ranged between 0.36-2.30 and a positive correlation was found between the indices. Our results contribute to the outcomes of Erdoğan (2009) and Korkmaz (2005) As indicated in Table 6, the differences among years, genotypes, and year*genotypes interactions were significant with regard to SDI value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotypes for FDI at the boll opening stage of 50-60%, ranged from 0.71 for an inbred line called 58 to the value of 1.15 for the Çukurova-1518 variety. According to Baran (2022), the leaf-disease severity varied between 0.12-3.09 at 50-60% at the boll opening period, whilst stem crosssection values ranged between 0.36-2.30 and a positive correlation was found between the indices. Our results contribute to the outcomes of Erdoğan (2009) and Korkmaz (2005) As indicated in Table 6, the differences among years, genotypes, and year*genotypes interactions were significant with regard to SDI value.…”
Section: Resultsmentioning
confidence: 99%
“…The need for improving significant strategies against cotton wilt has emerged. Thus, the use of resistant varieties derived from genetic resources has been considered the most practical and effective way of managing the disease (Baran et al 2022). Marani and Yaacobi (1976) observed that appropriate scanning for wilt resistance in Israel appears practical by examining foliar symptoms throughout the second part of the bloom period when the area is uniformly infected by the fungus under convenient temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Two diploid species Gossypium herbaceum (Levant or Arabian cotton) and Gossypium arboreum (Desi cotton) and two allotetraploid species Gossypium barbadense (Sea Island cotton) and Gossypium hirsutum (Upland cotton) are cultivated globally (Egan and Stiller, 2022). Among them, G. hirsutum is the most widespread and encompasses 95% of global cotton production and is also the main target of cotton breeding (Baran et al, 2022;Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%